A study on teachers’use of Vietnamese in English lessons at An Duong high school, Hai Phong = Nghiên cứu về việc sử dụng tiếng Việt của giáo viên trong các giờ dạy tiếng Anh tại trường THPT An Dương, Hải Phòng. M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Sinh (University of Languages and International Studies, 2017)
51 p. + CD-ROM